High Power Figure‐of‐Merit, 10.6‐kV AlGaN/GaN Lateral Schottky Barrier Diode with Single Channel and Sub‐100‐µm Anode‐to‐Cathode Spacing (Small 37/2022). Issue 37 (15th September 2022) - Xu, Ru; Chen, Peng; Zhou, Jing; Li, Yimeng; Li, Yuyin; Zhu, Tinggang; Cheng, Kai; Chen, Dunjun; Xie, Zili; Ye, Jiandong; Liu, Bin; Xiu, Xiangqian; et al.
Abstract : Schottky Barrier Diodes GaN is a promising candidate for next‐generation power electronic devices, but its potential is far from being realized. In article number 2107301, Peng Chen, Rong Zhang, Youdou Zheng, and co‐workers demonstrate a high power figure‐of‐merit, 10.6‐kV AlGaN/GaN lateral Schottky barrier diode with single channel, and sub‐100‐μm anode‐to‐cathode spacing without any other additional structures, which gives a clear and positive answer that GaN can be used in ultra‐high voltage applications.